THE CAUSE-EFFECT TECHNIQUE IN TEACHING RECOUNT WRITING - Asrifan, Andi; Muthmainnah, Muthmainnah; Al-Yakin, Ahmad; Sahabuddin, Chuduriah; Haedar, Haedar (Study Program of English Literature, 2018)
The objective of the research was to find out whether or not the use of the cause-effect technique can to improve students’ skill for eight grade students of SMP Negeri 1 Pancarijang and find out whether or not the use of cause-effect technique interested to students’ writing skill for eight grade students of SMP Negeri1 Pancarijang. This research employed the pre-experimental method with one group pre-test and post-test. The population of this research was the eight grade students of SMP Negeri 1 Pancarijang in academic years 2014-2015. The instrument used in this research was writing test and questionnaire. The result of this research showed that the pre-test got the mean score (40.00) while the post-test got mean score (65.00). This showed that there was a significant difference between pre-test and post-test.The result of the p.value was lower than alpha (α) 0.000 0.05. It means that H1 was accepted and H0 was rejected and the mean score by interest (76.85). It means the students interested in the technique.